За рулем женщина: напутствия начинающему водителю / С. Гросзова - Гросзова Сыльва (Транспорт, 1991)
Экземпляры: ф.7 (1993) / Инвентарный номер: 36695 / Цена: / Сис.шифр: 39.335 / Авт.знак: Г 88 / ГРНТИ: 73.31 / ББК: 39.335-082.02